Subtle impact of price controls on domestic oil production - Smith, Rodney T.; Phelps, Charles E. (American Economic Review, 1978)
The effects of price controls on oil production are examined for the period 1974 to 1976 and found to have had a negative elasticity in respect to world prices. The analysis considers the many regulatory changes that took place during the period and differentiates between the effects on independent and integrated producers and between production on old and new properties. New-property production reflects new exploration and expansion. The report concludes that, while controls may have caused initial increases in production, they were probably responsible for the subsequent decline. A supply curve has developed over the recent past that will result in a larger proportion of U.S. capital being transferred to the Organization of Petroleum Exporting Countries when future world prices increase.